2015
DOI: 10.1016/j.enmm.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil quality in response to short-term application of municipal sewage sludge in a typic haplustept under cowpea-wheat cropping system

Abstract: a b s t r a c tRecycling of sewage sludge as an organic amendment and source of macro-and micro-nutrient in agricultural fields can be a potential option for proper disposal of organic wastes. A field experiment was conducted at the experimental farm of Indian Agricultural Research Institute, New Delhi, to examine the short-term effect of municipal sewage sludge application on soil physical, chemical and biological properties of a sandy loam soil (typic haplustept) under cowpea-wheat cropping system. Control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 30 publications
4
22
1
3
Order By: Relevance
“…Likewise, Lazcano et al () and Liu et al () recorded greater values of soil C (both total and dissolved organic C) after short‐term application of compost. Additionally, Mondal et al () reported higher aggregate associated organic matter in response to short‐term application of organic waste. Plant available N, P, K, (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Lazcano et al () and Liu et al () recorded greater values of soil C (both total and dissolved organic C) after short‐term application of compost. Additionally, Mondal et al () reported higher aggregate associated organic matter in response to short‐term application of organic waste. Plant available N, P, K, (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The use of organic residues on agricultural land has been increasingly common (Barcellos et al, 2015;Mondal et al, 2015). In Brazil, the states that most use sewage sludge for agricultural purposes are: Paraná, São Paulo and Rio Grande do Sul (Sampaio, 2010).…”
Section: Dalpisol M Et Almentioning
confidence: 99%
“…Between 2007 and 2010 the sewage treatment plants in the Curitiba metropolitan region allocated 33,404 Mg (dry basis) of sanitized sewage sludge for use on 2,288 hectares of agricultural areas (Bittencourt et al, 2014). Studies have found that the sewage sludge have significant amounts of some elements essential to plants, such as Zn and Cu (Fia;Matos;Aguirre, 2005;Yada et al, 2015), and which can improve physical and biological soil properties (Bonini;Alves;Montanari, 2015;Mondal et al, 2015).…”
Section: Dalpisol M Et Almentioning
confidence: 99%
“…Since sewage sludge contains high amounts of heavy metals and pathogenic bacteria, its further application as an organic fertilizer for food crops is restricted in all European Uunion countries and its extensive use as organic fertilizer is still problematic (Kelessidis, Stasinakis, 2012;Latare et al, 2014). Mondal et al (2015) have reported that short-term application of sewage sludge has effect on different soil properties, particularly on soil fertility improvement. Soil microbial activity, microbial diversity and fertility are closely related, as during the process of sewage sludge mineralization the released mineral nutrients become available and readily absorbed by soil microorganisms and plants (Ros et al, 2003).…”
Section: Introductionmentioning
confidence: 99%